Degradation of democracy with the existence of a single candidate for regional head elections in Indonesia - Syaiful Rohman; Marthen Napang; Puspitasari Puspitasari (Faculty of Social and Political Science, Universitas Airlangga, 2022)
Regional head elections are part of the implementation of a democracy which is essentially indicated by political participation. The political elite at the central government also influences political competition in the regions. Every regional head election has to have a recommendation letter from the central board of the political party. The recommendation letter is a requirement for candidates for regent or mayor who will register to the General Election Commission (KPU). The general elections for regional heads are carried out to meet the demands of the community to elect their regional leaders directly with the spirit of democracy. Political elites often misuse democracy in pursuing power for personal or group interests so that a single candidate appears in the regional head elections. This study analyzes the relationship between the political elites and a single candidate using qualitative methods with descriptive analysis based on credible data sources. The results of this study stated that the political elite manipulate a significant role in gathering all-party support with a separate agreement so that a single candidate emerged in the regional head elections. This study concludes that the existence of a single candidate in the regional head elections results in a degradation in the democracy in Indonesia.